An Automated Method for the Study of Human Reliability in Railway Supervision Systems - Ferlin, Antoine; Qiu, Siqi; Bon, Philippe; Sallak, Mohamed; Collart Dutilleul, Simon; Schon, Walter; Cherfi-Boulanger, Zohra (IEEE transactions on intelligent transportation systems, 2018)
This paper presents an original experimental protocol, which aims to study human reliability in railway systems by computing the human error probability (HEP) of human operators. The experiment is conducted on a railway traffic management system that places operators in simulated situations involving railway failures. The obtained experimental result is analyzed first by two classical human reliability analysis methods to estimate the HEP of each subject. Then, a model of human operators using valuation-based system is proposed. Finally, a methodology automatically populates the proposed model by allowing the verification of temporal properties on the simulation trace.